تسخير تقنيات الذكاء الاصطناعي لتطوير الرعاية الصحية - بوقرة,سامية (University of Eloued جامعة الوادي, 2024)
ملخص: تهدف هذه الدراسة الى تحديد أهمية تسخير تقنيات الذكاء الاصطناعي لتطوير وتحسين الرعاية الصحية نظرت لما احدثته هذه الأخيرة من تطورات في جميع المجلات وليس المجال الصحي فقط، من خلال دراسة تحليلة لتطبيق " أطباء الجزائر"، وذلك للإجابة على الإشكالية التالية: فيما تتمثل أهمية التطبيق الذكي " أطباء الجزائر" في تطوير الرعاية الصحية ؟، وقد تم الاعتماد في هذه الدراسة على المنهج التحليلي، ومن اهم النتائج المتوصل اليها هو ان تطبيق " أطباء الجزائر" من اهم تطبيقات الذكاء الاصطناعي التي تضم قاعدة بيانات متطورة تحمل العديد من الخدمات التي تساهم في تطوير الرعاية الصحية وتعزيز التواصل المستمر والفعال بين الفاعلين في المجال ) أطباء، مرضى، مهنيي الصحة، الحماية المدنية... وغيرها Abstract: This study aims to determine the significance of harnessing artificial intelligence technologies to develop and enhance healthcare, considering the substantial advancements brought about by these technologies across various fields, including healthcare. Through an analytical study of the "Doctors of Algeria" application, the study seeks to answer the following research question: What is the importance of the "Doctors of Algeria" smart application in developing healthcare? The study adopts an analytical methodology, and one of the key findings is that the "Doctors of Algeria" application is one of the most significant artificial intelligence applications, featuring an advanced database that offers numerous services contributing to the development of healthcare and the promotion of continuous and effective communication among stakeholders in the field (doctors, patients, healthcare professionals, civil protection, and others).
تطبيق أطباء الجزائر أنموذجا
Keywords: الذكاء الاصطناعي; الرعاية الصحية; Technology; Artificial Intelligence; Health; Healthcare; Patients